2007
DOI: 10.1111/j.1744-7429.2007.00280.x
|View full text |Cite
|
Sign up to set email alerts
|

Yeasts Isolated from Neotropical Wood‐Boring Beetles in SE Peru

Abstract: Some temperate wood‐boring cerambycid beetles harbor intracellular gut yeasts believed to augment host nutrition, but species belonging to the subfamily Lamiinae are thought to lack endosymbionts. Almost 49 percent of Neotropical cerambycid species are lamiines, therefore, comparatively few rain forest species would be expected to host symbiotic gut yeasts. This study reports the isolation of gut yeasts from closely related Neotropical lamiines. We investigated species that feed on trees in the Brazil nut fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 45 publications
(61 reference statements)
0
18
0
Order By: Relevance
“…Suh et al (2005b) analysed 650 yeast isolates from the digestive tracts of beetles in 27 families (including many fungus feeders) and recognized at least 45 yeast clades. In an initial survey of gut yeasts from Neotropical wood-boring beetles, Berkov et al (2007) sampled 18 beetles at a single locality and 34 isolates yielded six gut yeasts, with an additional two yeasts from body exteriors. Mankowsky & Morrell (2004) reported 18 species in 11 genera from the intrabuccal pocket, exoskeleton and frass of wooddwelling carpenter ants (Camponotus vicinus Mayr) collected at two locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suh et al (2005b) analysed 650 yeast isolates from the digestive tracts of beetles in 27 families (including many fungus feeders) and recognized at least 45 yeast clades. In an initial survey of gut yeasts from Neotropical wood-boring beetles, Berkov et al (2007) sampled 18 beetles at a single locality and 34 isolates yielded six gut yeasts, with an additional two yeasts from body exteriors. Mankowsky & Morrell (2004) reported 18 species in 11 genera from the intrabuccal pocket, exoskeleton and frass of wooddwelling carpenter ants (Camponotus vicinus Mayr) collected at two locations.…”
Section: Discussionmentioning
confidence: 99%
“…The yeasts are maternally transmitted during oviposition and ingested when first intar larvae eat the eggshell (Douglas, 1989). Recent studies of several Neotropical wood-boring cerambycids found no support for strict vertical transmission, but larvae inhabiting the same branch sometimes gave rise to the same yeast (Berkov et al, 2007). If yeasts are primarily horizontally transmitted and part of a facultative, multispecies symbiosis, we would expect greater variability among yeasts isolated from conspecific insects.…”
Section: Ecological Associationsmentioning
confidence: 99%
“…In ovipositing females, the symbiontcon taining secretion is transported via flapcovered canals on the ovipositor surface ("Vaginalta schen" of Schomann 1937) to the ovipositor tip, and is pressed out by and smeared on the chorion of the egg being laid; the symbionts are ingested with the chorion by the hatching larva. Both structures were almost always absent in Lamiinae and Semenova & Danilevsky (1977) proposed secondary loss of endosymbiotic yeast associations in that subfam ily, yet luminal gut yeasts apparently related to some cerambycid endosymbionts were found also in lamiines (Berkov et al 2007;Calderon & Berkov 2012). Grinbergs (1962) found yeastlike microorganisms morphologi cally, biochemically and serologically very simi lar to some intracellular symbionts of European lepturines both in gut lumens and external envi ronment of some Prion inae and Cerambyc inae in Chile (where the subfamilies with larval midgut mycetomes do not occur), and the evolution of the intracellular symbiosis and specific transmission mechanism was probably via luminal gut com mensals.…”
Section: Cerambycidae Latreille 1802mentioning
confidence: 98%
“…The presence of xylose-and cellobiose-fermenting yeasts in the gut or specialized mycangia of some woodingesting beetles (e.g. Cerambycidae, Lucanidae, Passalidae) has been taken as evidence that beetles may receive a nutritional benefit from yeast symbionts that aid in the digestion of cellulose in the insect gut [104][105][106][107].…”
Section: Yeasts As Food Sourcesmentioning
confidence: 99%